PENGUATAN PENYIAPAN KOMPETENSI LULUSAN SMK TEKNIK LOGISTIK YANG DIBUTUHKAN INDUSTRI LOGISTIK - Vina Dwiyanti (Lentera Karya Edukasi, 2021)
There are not many Vocational High Schools (SMK) in the logistics sector, Vocational Schools have the aim of preparing students to be able to work, continue studies, entrepreneurship (BMW). These three objectives need to be prepared with competencies that are in accordance with the needs of the logistics industry. This readiness needs to be adjusted to the demands of the logistics industry. The follow-up study method carried out on Community Service (PkM) at the Logistics Engineering Vocational School aims to see the suitability of the needs and demands of the logistics industry and the conditions that exist in the Logistics Engineering Vocational School. The results of this PkM indicate that there is a demand for several special competencies, both technical skills, soft skills and hard skills and the need for industrial involvement and cooperation in learning at Logistics Engineering Vocational Schools to prepare Logistics Engineering Vocational School graduates that are in accordance with the needs of the logistics industry.